2015
DOI: 10.1175/jas-d-14-0051.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Tropical Cyclone Feedback on the Intensity of the Western Pacific Subtropical High to Microphysics Schemes

Abstract: The Advanced Research version of Weather Research and Forecasting (WRF-ARW) Model is used to examine the sensitivity of a simulated tropical cyclone (TC) track and the associated intensity of the western Pacific subtropical high (WPSH) to microphysical parameterization (MP) schemes. It is found that the simulated WPSH is sensitive to MP schemes only when TCs are active over the western North Pacific. WRF fails to capture TC tracks because of errors in the simulation of the WPSH intensity. The failed simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 100 publications
1
17
0
Order By: Relevance
“…Yet which influence plays a major role in the storm motion remains unknown. As discussed in Sun et al [] and Sun et al [], the anvil clouds could change the microphysical latent heating over the edge of the WPSH, which subsequently affects the WPSH and TC motion. Meanwhile, the TC movement often deviates from the large‐scale steering flow due to the beta‐effect propagation (BEP), which depends on the mean relative angular momentum and thus is highly sensitive to the outer wind structure of a TC [ Holland , ; Fiorino and Elsberry , ; Carr and Elsberry , ].…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…Yet which influence plays a major role in the storm motion remains unknown. As discussed in Sun et al [] and Sun et al [], the anvil clouds could change the microphysical latent heating over the edge of the WPSH, which subsequently affects the WPSH and TC motion. Meanwhile, the TC movement often deviates from the large‐scale steering flow due to the beta‐effect propagation (BEP), which depends on the mean relative angular momentum and thus is highly sensitive to the outer wind structure of a TC [ Holland , ; Fiorino and Elsberry , ; Carr and Elsberry , ].…”
Section: Introductionsupporting
confidence: 91%
“…Previous studies have indicated that the storm size affects its motion not only by changing the large‐scale environmental flow but also by influencing the BEP [ Holland , ; Fiorino and Elsberry , ; Carr and Elsberry , ; Bu et al ., ; Sun et al ., , ]. Figure compares the storm track simulated in the sensitivity experiments with the JTWC best track of Songda.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations